Effects of posture in hiatus hernia as studied by oesophageal pH measurement. Issue 6 (November 1971) - Habibulla, K. S.; Ammann, J. F.; Collis, J. Leigh
Abstract : The use of postural restriction in the treatment of patients with hiatus hernia has been analysed using continuous oesophageal pH measurements. It appears that it is not effective in the prevention of reflux of acid. The percentage of the time during which oesophageal pH remains below 5 is not significantly different when comparison is made during periods of sitting and lying. The frequency of reflux episodes is actually greater in the sitting position, but the duration of each reflux episode is significantly shorter than when lying. It is suggested that the undoubted symptomatic benefit derived by hiatus hernia patients from adopting the sitting position is explained by improved clearance of regurgitated acid.